THE EFFECT OF SALES GROWTH, CAPITAL STRUCTURE, AND INSTITUTIONAL OWNERSHIP ON FIRM VALUE (Empirical Study of Consumer Non-Cyclical Food and Beverage Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period) - Siti Azizah; Rahma Wiyanti (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study aims to determine the influence of sales growth, capital structure, and institutional ownership on firm value in consumer non-cyclicals sector companies, specifically in the food & beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. Firm value in this study is measured using the Price to Book Value (PBV) ratio. The research method used is quantitative. The data used are secondary data in the form of annual financial reports obtained from the official website of the Indonesia Stock Exchange. The sampling method used is purposive sampling based on several criteria relevant to the research. The final sample consists of 16 companies with a total of 80 observations. The data analysis technique used is panel data regression with the assistance of EViews 12 software. The results of the study indicate that simultaneously, sales growth, capital structure, and institutional ownership have a significant effect on firm value. Partially, capital structure and institutional ownership have a significant effect on firm value, while sales growth does not have a significant effect.